Antioxidant compounds in the seaweed Gelidiella acerosa protects human Peripheral Blood Mononuclear Cells against TCDD induced toxicity. (April 2015) - Ilavarasi, K.; Chermakani, P.; Arif Nisha, S.; Sheeja Malar, D.; Pandima Devi, K.
Abstract 2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin (TCDD) is a persistent environmental toxin formed as an unintentional by-product of incomplete combustion. Several therapeutic approaches have evolved to combat its toxicity since it elicits immunotoxicity, neurotoxicity, hepatotoxicity, carcinogenicity and lethality. Search for drugs from natural resources especially from seaweeds has become intense due to their enormous pharmacological potential. Hence, the present study aims at revealing the protective effect of methanolic extract of G. acerosa (MEGA) in Peripheral Blood Mononuclear Cells (PBMC) against TCDD induced toxicity, by assessing the antioxidant, anti-apoptotic and cytoprotective activities. The results of antioxidant assays suggests that MEGA reverted TCDD induced toxicity by causing an alteration in the levels of antioxidant enzymes (Catalase [CAT], Superoxide dismutase [SOD], Glutathione peroxidase [GPx], Glutathione-S-transferase [GST]) and Glutathione [GSH]. The results of lipid peroxidation assay and protein carbonyl content reveal that MEGA protects PBMC from TCDD induced macromolecular damage. MEGA was found to exhibit significant (p < 0.05) anti-apoptotic activity as verified by evaluation of mitochondrial membrane potential and AO-EtBr dual staining. In addition, PBMC co-treated with MEGA prevented TCDD induced oxidative DNA damage. Levels of phase-I detoxification enzymes determined by EROD assay and semi-quantitative RT-PCR showed that TCDD up-regulates the expression of CYP1A1 and upon co-treatment with MEGA, the expression got slightly decreased suggesting its protective role. Preliminary phytochemical analysis demonstrates that the extract is rich in cardiac glycosides and terpenoids. LC-MS analysis revealed the presence of antioxidants including caffeic acid, phytol and mannoheptulose in MEGA, which could be attributed for the observed protective effect against TCDD induced toxicity.